Fifteen Years Controlling Unwanted Thoughts: A Systematic Review of the Thought Control Ability Questionnaire (TCAQ) - Feliu-Soler, Albert; Pérez-Aranda, Adrián; Montero-Marín, Jesús; Herrera-Mercadal, Paola; Andrés-Rodríguez, Laura; Angarita-Osorio, Natalia; Williams, Alishia D.; Luciano, Juan V. (Frontiers in Psychology, 2019)
Thought control ability is a vulnerability factor implicated in the etiology and maintenance of emotional disorders. This manuscript aims to systematically review the use and psychometric performance of the Thought Control Ability Questionnaire (TCAQ), designed to assess people’s ability to control unwanted thoughts. Three electronic databases were searched for papers administering the TCAQ published in indexed peer-reviewed journals. Data (participants characteristics, country, study design, etc.) were extracted from the results for qualitative synthesis. The TCAQ’s content validity, dimensionality, internal consistency, test-retest reliability, convergent/divergent validity, floor/ceiling effects, and interpretability were summarized. Two reviewers independently screened articles and assessed quality taking COSMIN criteria into account. Finally, the review included 17 papers. The TCAQ has been administered to healthy individuals, students, and adult patients, in six languages from nine countries. We found that the TCAQ, and its shorter versions, demonstrate robust reliability and adequate content validity. Of interest is the TCAQ’s capacity to predict performance in diverse experimental tasks focused on thought control. The TCAQ unidimensionality has been supported in exploratory and confirmatory factor analyses. Regarding construct validity, the TCAQ is significantly related to a wide range of psychopathological measures of anxiety, worry, depression, obsessive-compulsive symptoms, etc. However, as only a few of the included studies had a longitudinal design, we are unable to draw firm conclusions about the measure’s temporal stability. Moreover, psychometric aspects such as factorial invariance across different samples have not been analyzed. Despite these limitations, based on available psychometric evidence we can recommend using the TCAQ for measuring perceived control of unwanted thoughts.